Teachers' perceptions of the brazilian curriculum reform, PISA and mathematics literacy - Emilly Gonzales Jolandek; Ana Lúcia Pereira (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The present work is the result of a master's research, guided by the following question: what are the perceptions that teachers of Mathematics of Basic Education have about BNCC, about PISA and about what is mathematical literacy proposed in PISA and BNCC? The article has a mixed nature and the data were collected through questionnaires, applied to Mathematics teachers who work in the Public Network of the State of Paraná. Data analysis took place through Content Analysis and Cluster Analysis. We obtained four clusters that allowed us to verify that the teachers knew the BNCC, but many did not read the Mathematics chapter. Regarding PISA, many teachers were not aware of this assessment. We found that teachers do not know if there are relationships between PISA and BNCC, as well as most teachers confused math literacy with math literacy.